Zebrafish TRIM25 Promotes Innate Immune Response to RGNNV Infection by Targeting 2CARD and RD Regions of RIG-I for K63-Linked Ubiquitination - Jin, Yilin; Jia, Kuntong; Zhang, Wanwan; Xiang, Yangxi; Jia, Peng; Liu, Wei; Yi, Meisheng (Frontiers in Immunology, 2019)
RIG-I-like receptors (RLRs) play important roles in response to virus infection by regulating host innate immune signaling pathways. Meanwhile, the RLRs signaling pathway is also tightly regulated by host and virus to achieve the immune homeostasis between antiviral responses and virus survival. Here, we found that zebrafish TRIM25 (zbTRIM25) functioned as a positive regulator of RLRs signaling pathway during red spotted grouper nervous necrosis virus (RGNNV) infection. Post RGNNV infection, zbTRIM25 expression was obviously inhibited and ectopic expression of zbTRIM25 led to enhanced expression of RLRs signaling pathway related genes. Overexpression and knockdown analysis revealed that zbTRIM25 promoted zebrafish RIG-I (zbRIG-I) mediated-IFN signaling and inhibited RGNNV replication. Mechanistically, zbTRIM25 bound to zbRIG-I, in particular, the SPRY domain of zbTRIM25 interacted with the tandem caspase activation and recruitment domains (2CARD) and repressor domain (RD) regions of zbRIG-I. zbTRIM25 promoted the K63 polyubiquitination of 2CARD and RD regions of zbRIG-I. Furthermore, zbTRIM25-mediated zbRIG-I activation of IFN production was enhanced by K63-linked ubiquitin, indicating zbTRIM25-mediated zbRIG-I polyubiquitination was essential for RIG-I-triggered IFN induction. In conclusion, these findings reveal a novel mechanism that zbTRIM25 positively regulates the innate immune response by targeting and promoting the K63-linked polyubiquitination of zbRIG-I.